The issue of gender and race in career progress and labor market - Sandra Maria Cerqueira da Silva; Angela Lucas (REGE Revista de Gestão, 2018)
Purpose - The text is the result of research carried out at undergraduate and post-graduate levels. This think-box corresponds to a collection of ideas and reflections debated in a roundtable that discussed issues related to access and career limitations for women, especially for black women. In this sense, the purpose of this paper is to present, analytically, data that demonstrate the unequal conditions by gender and race. Design/methodology/approach - The selected approach was qualitative in a critical perspective. Findings - The discussion elicits important social markers to establish difference, and thereby promote exclusion. Reflection on these issues needs to go beyond academic boundaries and reach the business community, perhaps worldwide, sensitizing them to the urgent need to revise biased methods and procedures that are crystallized. It is necessary to create conditions for a more balanced and humane look at women, especially black women. And, in this way ensure fairness in the treatment of people in all aspects, especially in educational spaces and the labor market. Research limitations/implications - The difficulty in identifying some systematized data limits the condition of broadening our view to points that have been discussed in the text, such as where are the 6 percent of black executive women. Practical implications - It is hoped that this paper may elicit reflections on the current social exclusionary context, and subsidize practices on a more equitable basis observing gender and race. Social implications - Socially speaking, it is hoped that this discussion could guide actions to eliminate or reduce the gap, mainly through specific public policies to address the issues of women in Brazil. Originality/value - It is the parallel discussion of gender and race in the business sector, where the subjects were scarcely explored, and the critical theory was used as a basis of analysis.